Hello there, I'm having trouble proving this by induction(adsbygoogle = window.adsbygoogle || []).push({});

1. The problem statement, all variables and given/known data

[itex]\frac{1}{1(2)} + 1\frac{1}{2(3)}+...+\frac{1}{n(n+1)} = \frac{n}{n+1}[/itex]

2. Relevant equations

For the base case n=1

[itex]\frac{1}{1(2)}=\frac{1}{1+1} = \frac{1}{2} = \frac{1}{2}[/itex]

[itex]\frac{k}{k+1} + \frac{1}{(k+1)(k+2)}[/itex] <- the second term would be the next integer

3. The attempt at a solution

[itex]\frac{1}{1(2)}+ \frac{1}{2(3)}+\frac{1}{k(k+1)} + \frac{1}{(k+1)(k+2)} = \frac{k+1}{(k+1)+1} = \frac{k}{k+2} + \frac{1}{k+2}[/itex]

I don't know where to go from here, any help would be appreciated

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Help with induction proof

**Physics Forums | Science Articles, Homework Help, Discussion**